Effect of urdbean (Vigna mungo) cultivars and phosphorus levels on dynamics of soil phosphorus fractions and enzyme activity - DUTTA, ASIK; DAS, KRISHNASHIS; SENTHILKUMAR, M; KUMAR, NARENDRA; NATH, CHAITANYA P (The Indian Journal of Agricultural Sciences, 2024)
A field experiment was conducted during the rainy (kharif) seasons of 2019 and 2020 at ICAR-Indian Institute of Pulses Research, Kanpur, Uttar Pradesh to study the impact of soil inorganic phosphorus fractions and enzyme activity in different urdbean [Vigna mungo (L.) Hepper] cultivars. Experiment was conducted in a randomized block design (RBD) with 4 replications with two urdbean cultivars, viz. IPU-2-43 and Uttara. Experimental results suggest, higher sol-P content (6 and 14% in 2019 and 2020, respectively) under Uttara than IPU 2-43 under low P-plots whereas, no prominent change of the same was recorded under normal P-plots. Similar to sol-P, the content of Ca2-P has jumped significantly in Uttara than IPU 2-43. However, Uttara recorded higher acid and alkaline phosphatase activity as compared to IPU 2-43. In low-P plots the activity of acid phosphatase was higher by 12% (2019) and 10% (2020) in case of Uttara than IPU 2-43. Under low P soils the productivity of Uttara was significantly higher (~12% and ~9% in 2019 and 2020, respectively) than IPU 2-43. Therefore, based on the findings it can be said that with higher soluble P and productivity, the performance of Uttara was better over IPU 2-43 under low-P condition.